2022
DOI: 10.1209/0295-5075/ac8446
|View full text |Cite
|
Sign up to set email alerts
|

Chiral oscillations

Abstract: The solutions of the Dirac equation are given in terms of bispinors, four-component objects which include both spin and chirality as internal degrees of freedom. For massive particles, the Dirac equation couples components of the bispinor with different chiralities, yielding chiral oscillations. This phenomenon can be particularly relevant for recent proposals aimed at measuring non-relativistic cosmic neutrinos, and can find analogous in Dirac-like systems, such as graphene. In this paper, a concise review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…0, they give the Pontecorvo oscillation formulas. Note that the above corrections are of the same order of the chiral oscillation terms [36] which have been not considered here and are also vanishing in the relativistic limit.…”
Section: The Generator Of the Mixing Transformation And The Flavor Va...mentioning
confidence: 99%
“…0, they give the Pontecorvo oscillation formulas. Note that the above corrections are of the same order of the chiral oscillation terms [36] which have been not considered here and are also vanishing in the relativistic limit.…”
Section: The Generator Of the Mixing Transformation And The Flavor Va...mentioning
confidence: 99%
“…In [7] it is shown that starting with an initial state at t = 0 with both negative chirality and negative helicity…”
Section: Chiral Oscillationsmentioning
confidence: 99%
“…In fact, the Dirac equation, describing the temporal evolution of a massive fermion, includes a term which couples left and right-handed components of the bispinor, which yields chirality oscillations [3,4], characterized by the ratio between the momentum and the mass. Chiral oscillations have been studied recently [5][6][7] in connection with their possible relevance for relic neutrinos of the CνB background [8] and more in general in the non-relativistic regime. In particular, the effects of chiral oscillations on the spin-spin correlations of a lepton-antineutrino pair has been investigated in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Significant attention has also been given to the study of possible applications in graphene-based entanglement [50], quantum memory [51,52] and quantum teleportation [53]. Recently, many research works have studied the dynamics of entanglement in a graphene layer system [50,[54][55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%